Diet and Feeding Habits of Cyprinus carpio in Relation with Water Quality of Integrated Rice-Fish Farming Ecosystem - Mondol, Md. Mostafizur Rahman; Rahman, Md. Mosaddequr; Nahar, Dil Afroz; Ahamed, Ferdous; Sarker, Md. Al-Amin; Subba, Bharat Raj; Hossain, Md. Yeamin (Our Nature, 2014)
This study describes the diets and feeding habits of Cyprinus carpio in integrated rice-fish farming system in the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh, Central Bangladesh during May 1999 to August 1999. Percentage of frequency of occurrence and percentage in number methods were applied for the qualitative and quantitative estimation of plankton. The water quality parameters recorded during the study were within the suitable range for optimal fish growth and plankton populations were also abundant in the water of the rice plots. The phytoplankton population recorded from the gut contents of C. carpio was under 4 groups (viz., Chlorophyceae, Euglenophyceae, Cyanophyceae, Bacillariophyceae) and the zooplankton under 3 groups (viz., Rotifera, Cladocera, Copepoda). Bacillariophyceae and Chlorophyceae were the dominant phytoplankton group while Rotifera was the dominant zooplankton group in the gut contents of C. carpio. This study also revealed that, gut contents of C. carpio was composed of 48.47% phytoplankton and 51.53% zooplankton indicating omnivorous nature of the fish. The availability of plankton population in the rice plots and the food and feeding habits of C. carpio suggest that, this fish could be a vital candidate for integrated rice-fish aquaculture.